An Online Experiment During COVID-19: Testing the Influences of Autonomy Support Toward Emotions and Academic Persistence - Wang, Yurou; Zhang, Jihong; Lee, Halim (Frontiers in Psychology, 2021)
Students’ academic persistence is a critical component of effective online learning. Promoting students’ academic persistence could potentially alleviate learning loss or drop-out, especially during challenging time like the COVID-19 pandemic. Previous research indicated that different emotions and autonomy support could all influence students’ academic persistence. However, few studies examined the multidimensionality of persistence using an experimental design with students' real-time emotions. Using an experimental design and the Contain Intelligent Facial Expression Recognition System (CIFERS), this research explored the dynamic associations among real-time emotions (joy and anxiety), autonomy support (having choice and no choice), self-perceived persistence, self-reliance persistence, and help-seeking persistence. 177 college students participated in this study online via Zoom during COVID-19 university closure. The results revealed that having choice and high intensity of joy could promote students’ self-reliance persistence, but not help-seeking persistence. Interestingly, students who perceived themselves as more persistent experienced more joy during experiment. The theoretical and practical implications on facilitating students’ academic persistence were discussed.